Happiness and well-being - Heathwood, Chris ca. 20./21. Jh (Cambridge elements, 2021)
This Element provides an opinionated introduction to the debate in moral philosophy over identifying the basic elements of well-being and to the related debate over the nature of happiness. The question of the nature of happiness is simply the question of what happiness is (as opposed to what causes it or how to get it), and the central philosophical question about well-being is the question of what things are in themselves of ultimate benefit or harm to a person, or directly make them better or worse off